Salvianolic acid B in fibrosis treatment: a comprehensive review - Liang, Qingzhi; Liu, Xiaoqin; Peng, Xi; Luo, Ting; Su, Yi; Xu, Xin; Xie, Hongyan; Gao, Hong; Chen, Zhengtao; Xie, Chunguang (Frontiers in Pharmacology, 2024)
Fibrosis is a public health issue of great concern characterized by the excessive deposition of extracellular matrix, leading to the destruction of parenchymal tissue and organ dysfunction that places a heavy burden on the global health care system due to its high incidence, disability, and mortality. Salvianolic acid B (SalB) has positively affected various human diseases, including fibrosis. In this review, we concentrate on the anti-fibrotic effects of SalB from a molecular perspective while providing information on the safety, adverse effects, and drug interactions of SalB. Additionally, we discuss the innovative SalB formulations, which give some references for further investigation and therapeutic use of SalB's anti-fibrotic qualities. Even with the encouraging preclinical data, additional research is required before relevant clinical trials can be conducted. Therefore, we conclude with recommendations for future studies. It is hoped that this review will provide comprehensive new perspectives on future research and product development related to SalB treatment of fibrosis and promote the efficient development of this field.